Measurement of motor conduction velocity with Hopf's technique in myotonic dystrophy. Issue 1 (January 1983) - Rossi, B; Sartucci, F; Stefanini, A; Pucci, G; Bianchi, F
Abstract : Hopf's technique was used to measure maximal and minimal motor nerve conduction velocities, and the percentage of fibres with intermediate velocity, in the posterior tibial nerve in patients with myotonic dystrophy. A reduction of maximal and minimal conduction velocities was found. The distribution of fibres with intermediate velocity was nearly identical to that of the control group and the dispersion values were normal. These data do not support the hypothesis that a primary disturbance of the motor neurons is responsible for the muscle changes in myotonic dystrophy. The reduction of the motor nerve conduction velocity, which was an inconstant finding, should not be considered an indication of a neurogenic aetiology of myotonic dystrophy, but only one of the many disorders of a multisystem disease.